INKONSISTENSI DAN DAMPAK KETIADAAN KODE ETIK DEWAN PERWAKILAN RAKYAT DAERAH (Studi Pada Dewan Perwakilan Rakyat Daerah Kabupaten Garut Periode 2014-2019): Array - Elly Nurlia; Ali Nurdin (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2021)
This research is based on the weak dynamics of implementing the legislative function in Garut Regency which results from chaotic inconsistencies due to the absence of a DPRD code of ethics as a guideline for implementing regional government in accordance with the mandate of the legislation. This has an impact in the form of the lack of regulations issued by the Garut Regency DPRD which leads to real needs, in addition to the many violations that are actually recorded in the DPRD code of ethics. This research uses qualitative methods with descriptive studies. The determination of informants was selected from the actors who intersect with the dynamics of governance by the Regional Representative Council (DPRD) of Garut Regency. Data collection used in-depth interviews, observation and documentation techniques. The results of the study reveal the fact that the implementation of regional government by the Garut Regency DPRD for the 20142019 period is still very far from the essence and expectations of the community. It can be seen from the magnitude of the inconsistency of the members of the legislative body, because during one period of office there was a utopia of establishing a code of ethics. Apart from the abnormal and weak function of the Honorary Board (BK) in maintaining the proper manner and relationship between DPRD. The domio effect of consistency and the absence of a code of ethics can be seen from the weak articulation of the aspirations of the community because of the 97 Regional Regulations produced during the five years (2014-2019 period) Garut DPRD only produced two regional regulations.